2019
DOI: 10.1002/mc.23127
|View full text |Cite
|
Sign up to set email alerts
|

Single‐nucleotide polymorphism rs13426236 contributes to an increased prostate cancer risk via regulating MLPH splicing variant 4

Abstract: A prostate cancer risk single-nucleotide polymorphism (SNP), rs13426236, is significantly associated with melanophilin (MLPH) expression. To functionally characterize role of the rs13426236 in prostate cancer, we first performed splicing-specific expression quantitative trait loci analysis and refined the significant association of rs13426236 allele G with an increased expression of MLPH splicing transcript variant 4 (V4) (P = 7.61E−5) but not other protein-coding variants (V1-V3) (P > .05). We then performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…MLPH is an important component involved in the transport of melanin, which contributes to visible pigmentation of hair and skin ( 49 , 50 ). While its role in cancer is not well understood, recent research has found that MLPH is associated with tumor development and metastasis in skin, breast, and prostate cancer ( 51 , 52 , 53 , 54 , 55 ). Meanwhile, several studies demonstrated that MLPH was highly expressed in lung adenocarcinoma but not in squamous cell carcinoma, indicating that MLPH could be a potential marker for differential diagnosis ( 56 , 57 , 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…MLPH is an important component involved in the transport of melanin, which contributes to visible pigmentation of hair and skin ( 49 , 50 ). While its role in cancer is not well understood, recent research has found that MLPH is associated with tumor development and metastasis in skin, breast, and prostate cancer ( 51 , 52 , 53 , 54 , 55 ). Meanwhile, several studies demonstrated that MLPH was highly expressed in lung adenocarcinoma but not in squamous cell carcinoma, indicating that MLPH could be a potential marker for differential diagnosis ( 56 , 57 , 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…These factors could be influenceable such as lifestyle and dietary habits but also not influenceable like genetic susceptibility [2,4]. Several studies prove that single nucleotide polymorphism (SNP) of some genes may contribute to an increased or decreased cancer risk [5,6]. Among those SNPs, the ABCB1/MDR1 gene seems to play an important role in tumor progression [7].…”
Section: Introductionmentioning
confidence: 99%
“…The PTEN gene has multiple SNPs and is a highly polymorphic gene, and pathogenic germline mutations are found in all 9 exons [20]. In recent years there are several reports that polymorphism can affect the process of alternative splicing, which lead to the occurrence and development of many human diseases [21][22][23]. The process of AS is affected by many factors, among which the in uence of the 3'and 5'splice site sequence of the branch point is common [24].…”
Section: Introductionmentioning
confidence: 99%